FILM EDIBEL ANTIBAKTERI BERBASIS ISOLAT PROTEIN KEDELAI DENGAN EKSTRAK KUNYIT DAN NANOPARTIKEL SENG OKSIDA - Imawati Eka Putri; Nugraha Edhi Suyatma; Harsi Dewantari Kusumaningrum (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Soy protein isolate (SPI) is one of the base materials for edible film production in addition to polysaccharide and lipid, but it does not have antibacterial activities. Incorporation of antibacterial agents may increase the functional properties of edible films. This research was aimed to determine the effects of zinc oxide nanoparticles (ZnO-NPs) and turmeric extract addition into soy protein isolate-based films on the physical, mechanical and antibacterial characteristics of the films. Edible films were prepared by dissolving 5 grams of SPI into 100 mL of distilled water followed by the addition of ZnO-NPs (0, 1, and 2.5% of the SPI weight) and/or added with turmeric extracts (0 and 2.5% of the SPI weight). The results showed that addition of ZnO-NPs and turmeric extracts into the films significantly increased the thickness and values of tensile strength, while addition of turmeric extract decreased the percent of films elongation. Addition of ZnO-NPs had a significant effect in decreasing the water vapor transmission rate (WVTR) values. The combination of ZnO-NPs and turmeric extracst had a considerable effects in inhibiting E.coli growth in the range of 2.25 mm to 3.18 mm. Meanwhile, addition of ZnO-NPs resulted in inhibition against E.coli in the range of 2.54 mm to 4.29 mm. Furthermore, this research showed that addition of ZnO NPs and turmeric extracts could improve the physical and mechanical properties of SPI-based film. The best films was obtained by using ZnO NPs at 2.5% which potentially can be used as an antibacterial packaging.